Training of health workers and traditional leaders on maternal and child nutrition and optimal practices for inclusion of animal-source foods in healthy diets in Uganda - Ouma, Emily A.; Ahumuza, Ronnie; Ahmed, Hardi; Omosa, Esther; Achandi, Esther; Ngalombi, Sarah; Ahumuza, Laura; Teufel, Nils; Molina, Teresa (International Livestock Research Institute, 2024)
An exploratory study conducted by the CGIAR’s Sustainable Animal Productivity for Livelihoods, Nutrition and Gender inclusion (SAPLING) work package 2 in March–April 2023 in Masaka, Mukono and Wakiso districts in Uganda showed nutrition knowledge gaps for both men and women livestock farmers. Results also revealed socio-cultural norms based on beliefs that hinder consumption of some animal-source foods (ASFs) for some members of the society, particularly children and women. For instance, some cultures hinder consumption of ASFs such as eggs, pork and certain types of fish for pregnant women. SAPLING in collaboration with stakeholders co-designed a social behaviour change communication (SBCC) intervention that goes beyond the provision of nutrition education to improve nutrition knowledge but also focuses on addressing norms to demystify consumption of ASFs by children and women of childbearing age. The intervention was implemented by health workers, specifically the village health teams (VHTs) through a cluster-randomized controlled trial design with three study arms in Mukono and Masaka districts as follows: